PENGARUH IKLIM KERJA TERHADAP SEMANGAT PEGAWAI KANTOR DINAS KEBERSIHAN DAN KEINDAHAN PASAR - Esi Komasanti; Puti Rafika Yuliasari; Epo Rindo (Fakultas Ekonomi Universitas IBA Palembang, 2021)
Work climate is a working condition that is in an office or place that is comfortable, quiet, and free to do work without any worries. A pleasant work climate will be created if human relations develop harmoniously. The condition of this harmonious atmosphere is very supportive of the employee's work performance. The existence of a comfortable and calm work climate allows employees to work better. The hypothesis proposed is that there is a strong influence between the work climate on the morale of the employees of the Office of Cleanliness and Market Beauty. The conclusion of this study is that there is a very strong influence between the work climate on the morale of the employees at the Office of the Office of Cleanliness and Market Beauty. Suggestions from the research are the need for serious attention regarding the application of the work climate so that the organization can really run well.